2015
DOI: 10.1007/s12011-015-0574-2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Dietary Copper on Serum Growth-Related Hormone Levels and Growth Performance of Weanling Pigs

Abstract: To investigate the effect of dietary copper on serum growth-related hormones levels and growth performance, a total of 60 weanling pigs were randomly assigned to six groups each containing 10 pigs, fed on basal diets supplemented with 0 (control), 100, 150, 200, 250, and 300 mg/kg copper sulfate for 80 days, respectively. The average daily gain (ADG), feed to gain ratio (F/G), feed intake and serum growth hormone (GH), insulin (INS), insulin-like growth factor 1 (IGF-1), and insulin-like growth factor-binding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 19 publications
3
7
0
Order By: Relevance
“…It has been believed that the growthpromoting effects of copper are related to the GH axis and might be generated by the stimulation of GH secretions [27]. Our study observed that serum GH increased in the HC group, similar to the results of a previous study which showed that high copper levels (100 to 300 mg•kg − 1 ) can increase serum GH concentrations in weaning pigs [28]. However, high levels of copper did not affect the serum IGF-1 in our study, unlike Wang's previous study, which found that dietary copper (250 mg•kg − 1 , CuSO 4 ) increased serum IGF-1 concentrations on days 20 and 40 for weanling pigs, with the rise in serum IGF-1 partly due to increased feed intake [29].…”
Section: Discussionsupporting
confidence: 90%
“…It has been believed that the growthpromoting effects of copper are related to the GH axis and might be generated by the stimulation of GH secretions [27]. Our study observed that serum GH increased in the HC group, similar to the results of a previous study which showed that high copper levels (100 to 300 mg•kg − 1 ) can increase serum GH concentrations in weaning pigs [28]. However, high levels of copper did not affect the serum IGF-1 in our study, unlike Wang's previous study, which found that dietary copper (250 mg•kg − 1 , CuSO 4 ) increased serum IGF-1 concentrations on days 20 and 40 for weanling pigs, with the rise in serum IGF-1 partly due to increased feed intake [29].…”
Section: Discussionsupporting
confidence: 90%
“…The third potential mechanism in terms of growth-promoting or feed efficiency-enhancing effect of high Cu supplementation could be exerted via a systemic route. Evidence has demonstrated that increasing Cu supplementation in weaning pigs could increase serum mitogenic activity, liver superoxide dismutase activity, and pituitary growth hormone mRNA concentrations ( Zhou et al, 1994a , 1994b ) and elevate serum growth hormone and insulin-like growth factor-1, as well as enhance ghrelin mRNA expression in fundic region of stomach, and growth hormone-releasing hormone and suppressing somatostatin mRNA expression levels in hypothalamus ( Yang et al, 2011 , 2012 ; Wang et al, 2016 ). These anabolic factors could be the strong determinants for Cu to promote growth and enhance feed efficiency in pigs, which may also explain the improved growth rate and feed efficiency in the overall nursery period in pigs fed diets containing Cu-MHAC in the current experiment.…”
Section: Discussionmentioning
confidence: 99%
“…Copper is an essential trace element in animals that is beneficial to hematopoiesis, growth, metabolism, and various important physiological activities of life [1]. For a long time, copper has been added to swine diets at high concentrations to reduce infection and promote growth, especially for weanling pigs [2,3]. However, high concentrations of copper in the diet may lead to organ damage of swine and pose a threat to the environment [4,5].…”
Section: Introductionmentioning
confidence: 99%